Large sliding regulation in van der waals layered nonlinear optical ternary chalcogenides - Qingchen Wu; Lei Kang; Jian Wu; Zheshuai Lin (npj Computational Materials, 2023)
Abstract Interlayer sliding modulation in van der Waals (vdW) layered materials opens opportunities to seek tunable applications for photonics and optoelectronics at the nanoscale. In this work, focusing on ternary chalcogenides, dozens of typical vdW layered materials with the formula of A2MZ4 (A, M = metal cation; Z = S/Se) were systematically classified and studied to illustrate the interlayer sliding modulation performance on nonlinear optical (NLO) effect and underlying mechanism. Based on first-principles analysis, the screened Cd2GeSe4 exhibits large second harmonic generation (SHG) deviation (>36 times between high- and low-SHG states) under sliding among all studied materials. This phenomenon arises from the polarization modulation induced by the vdW interlayer charge redistribution of two tetrahedral primitives in the ternary edge-sharing tetrahedral structures. Our findings present a strategy to substantially modulate NLO properties by altering the interlayer charge coupling which is commonly thought to be very weak in vdW layered materials.